Organizational Transformation - Assessing Value, Competency and Capability - Soin , DilJot (Gyan Management Journal, 2013)
In today's turbulent economy, many organizations across the globe embarked in organizational transformation initiatives from reductions in force to radical restructuring to enhance capabilities, to improve performance and provide competitive advantage/or business. Transforming the organization refers to any significant change made to an organization such as, restructuring an organization or reengineering an organization, changing the organizational culture and/or there is a significant change in the way business is done. In implementing business transformation initiatives, these organizations often face a significant stumbling block because of inability to prepare their employees to handle these change initiatives. Thus, one of the issues that need to be addressed in this scenario is resistance to change. The present paper makes contribution by examining the key elements organizatfonal transformation and impact of transformation on the workforce, strategic vision in terms of values and competencies of employees, effective change management strategies, common resistance to change and suggestive measures in dealing with resistance to organizational transformation.
Keywords: Organizational Transformation; Resistance to change